The influence of school inclusive education climate on physical education teachers’ inclusive education competency: The mediating role of teachers’ agency - Xue, Rui; Chai, Hongqin; Yao, Lei; Fu, Wangqian (Frontiers in Psychology, 2023)
Introduction Teachers’ inclusive education competency is the key to the successful implementation of inclusive education. Under the background of China’s vigorous development of inclusive education, the influence mechanism of inclusive education competency of Chinese physical education teachers has not been paid attention to. The present study concentrates on the relationships between school inclusive education climate, physical education teachers’ agency, and inclusive education competency. Methods Data were collected from 286 primary and junior high school physical education teachers through nationwide convenience sampling on the Internet in China by completing the School Inclusive Education Climate Scale, Physical Education Teachers’ Agency Scale, PE Teachers’ Inclusive Education Competency Scale. Results Results of structural equation modelling revealed that school inclusive education climate had a significant effect on physical education teachers’ agency. School inclusive education climate had a significant influence on physical education teachers’ inclusive education competency. The mediation effect of physical education teachers’ agency on the relationship between school inclusive education climate and inclusive education competency was significant as well. Discussion These results demonstrate that school inclusive education climate plays a direct and indirect role in promoting physical education teachers’ inclusive education competency.